A family of metainferential logics. Issue 1 (2nd January 2019) - Pailos, Federico Matias
ABSTRACT: We will present 12 different mixed metainferential consequence relations. Each one of them is specified using two different inferential Tarskian or non-Tarskian consequence relations:K 3, L P, S T orT S + . We will show that it is possible to obtain a Tarskian logic with non-Tarskian inferential logics, but also a non-Tarskian logic with Tarskian inferential logics. Moreover, we will show how some of these metainferential logics work better than the corresponding inferential rivals. Finally, we will show how these logics prove that it is not enough to work with inferences as pairs of sets of formulas to obtain a contractive logic.